Glycemic Control among Patients with Type 2 Diabetes Mellitus in Countries of Arabic Gulf - Al-Rasheedi, Ahmad Ali (International Journal of Health Sciences, 2015)
Â Â Â Type 2 diabetes mellitus is a growing, worldwide public health concern. The countries of Arabic Gulf appear to have a higher prevalence of diabetes than the global average. The recent and rapid socio-economic development of these countries has been associated with this rising prevalence. Although the rate of type 2 diabetes management based on glycosylated hemoglobin level in the countries of Arabic Gulf is labeled as poor, the outcomes are almost similar to those reported from elsewhere. Unfortunately, overweight and obesity are driving the global diabetes epidemic. A minority of patients with type 2 diabetes had a normal body weight which might make the control of diabetes difficult. Anyhow, Greater efforts are urgently needed to properly manage diabetes early in order to prevent short and long-term complications. Practical strategies aimed at more effective management of type 2 diabetes patients are strongly needed.